Sustainable Geography - Oliveras González, Xavier (Documents d'Anàlisi Geogràfica, 2013)
BRUNET, Roger (2011) Sustainable Geography Londres / Haboken: ISTE / Wiley, XXVI + 393 p. ISBN 978-1-84821-192-6